Pengaruh Mata Kuliah Statistik Terhadap Kualitas Penelitian Mahasiswa Tingkat Akhir - Siregar, Rizka Fahruza; Rahim, Rani; Purba, Oktaviana Nirmala; Rizqi, Nur Rahmi; Azis, Zainal (Indo-MathEdu Intellectuals Journal, 2025)
Statistics is an important basic subject in data processing and analysis, especially for academic research. This course is the main foundation for students to develop analytical skills to produce quality research. This research evaluates the contribution of statistics courses to the quality of final year student research at the State Islamic University of North Sumatra. The method used is quantitative with descriptive statistical analysis to see the relationship between mastery of statistics and research quality. Data was obtained through a questionnaire. The analysis technique used is quantitative descriptive with statistical tests. The results show a significant positive correlation between mastery of statistics and research quality, especially in preparation of proposals, data analysis, and interpretation of results. Students with a good understanding of statistics tend to produce higher quality research. These findings emphasize the importance of quality statistics learning to increase student research success through enriching material and data analysis practices.